MENINGKATKAN KEMAMPUAN MOTORIK KASAR MELALUI PARENTING SENAM MASAL IBU DAN ANAK PADA ANAK USIA DINI TK DHARMA WANITA BANGSAL KECAMATAN PESANTREN KOTA KEDIRI TAHUN PELAJARAN 2017/2018 - S. Edy Subroto (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2018)
This research is research in action (action research) because the research was done to solve the problem of learning in the classroom. Based on the results of the research conducted, note that there is an increase in the percentage of children starting from ketuntasan learn cycle I of 40%, an increase of 20%, as well as reaching ketuntasan on cycle II amounted to 85%. Thus the hypothesis in the study of the learning that goes through the mass gymnastics activities parenting mothers and children can improve motor rough early childhood kindergarten Dharma Wanita Ward Subdistrict Pesantren, Kediri is proving that hypothesis is accepted.